Effectiveness of a lifestyle modification programme in the treatment of depression symptoms in primary care - Aguilar-Latorre, Alejandra; Pérez Algorta, Guillermo; Navarro-Guzmán, Capilla; Serrano-Ripoll, María J.; Oliván-Blázquez, Bárbara (Frontiers in Medicine, 2022)
Background: Depression symptoms are prevalent in the general population, and their onset and continuation may be related to biological and psychosocial factors, many of which are related to lifestyle aspects. Health promotion and lifestyle modification programmes (LMPs) may be effective on reducing the symptoms. The objective of this study was to analyse the clinical effectiveness of a LMP and a LMP plus Information and Communication Technologies (LMP+ICTs), when compared to Treatment as Usual (TAU) over 6 months. The interventions were offered as an adjuvant treatment delivered in Primary Healthcare Centres (PHCs) for people with depression symptoms. Methods: We conducted an open-label, multicentre, pragmatic, randomised clinical trial. Participants were recruited from several PHCs. Those participants visiting general practitioner (GP) for any reason, who also met the inclusion criteria [scoring 10 to 30 points on the Beck II Self-Applied Depression Inventory] were invited to take part in the study. LMP consisted of six weekly 90-minute group sessions focused on improving lifestyle. LMP + ICTs replicated the LMP format, plus the addition of a wearable smartwatch to measure daily minutes walked and sleep patterns. A total of 188 participants consented to participate in the study and were randomised. We used linear mixed models, with a random intercept and an unstructured covariance to evaluate the impact of the interventions compared to TAU. Results: Both interventions showed a statistically significant reduction on depressive symptoms compared to TAU (b = -3.38, 95% CI= [-5.286, -1.474] p < 0.001 and b = -4.05, 95% CI= [-5.919, -2.197], p < 0.001). These reductions imply a moderate effect size. In the LMP+ICTs there was a significant increase regarding minutes walking per week (b = 99.77) and adherence to Mediterranean diet (b = .702). In the LMP there was a significant decrease regarding bad sleep quality (b = -1.24). Conclusion: LMPs administered in PHCs to people experiencing depression symptoms were effective on reducing these symptoms compared to TAU. They also have a positive impact on changing several lifestyle factors. These findings indicate that these interventions can be promising strategies for PHCs.